Boii - Taurisci Proceedings of the International Seminar, Oberleis-Klement, June 14th−15th, 2012 - Ramsl, Peter C. (Verlag der Österreichischen Akademie der Wissenschaften, 2016)
This volume is the result of a conference, which was held from June 14-15, 2012 at the Event Centre Schüttkasten in Klement-Oberleis, Lower Austria. The thematic focus of the contributions was the nature of contacts and relations between the settlement areas of the La Tène culture, which are associated with the Celtic tribes of the Boii and Taurisci on the basis of numismatic and written sources. The paradigm shifts in Iron Age archaeology and the veritable explosion of new archaeological materials and find contexts (coins, fibulae, Knotenringe, architecture and settlement features) have found their expression in this volume.